Frontal plane kinematics predict three-dimensional hip adduction during running. (September 2017) - Creaby, Mark W.; Le Rossignol, Scott; Conway, Zachary J.; Ageberg, Eva; Sweeney, Matthew; Franettovich Smith, Melinda M.
Abstract: Objectives: To investigate if frontal plane kinematics are predictive of three dimensional (3D) hip adduction and hip internal rotation during running. Study design: Cross-sectional. Setting: Biomechanics laboratory. Participants: Thirty healthy male runners aged 18–45 years. Main outcome measures: Two dimensional (2D) angles in the frontal plane (peak pelvic obliquity, peak hip adduction, peak femoral valgus, peak knee valgus and peak tibial valgus) and 3D hip adduction and hip internal rotation during stance phase of running were obtained. Results: Linear regression modelling revealed that peak 2D pelvic obliquity (a drop towards the contralateral leg) and peak femoral valgus significantly predicted 88% of the variance in peak 3D hip adduction (p < 0.001). Frontal plane kinematics however, were not predictive of peak hip internal rotation in 3D (p > 0.05). Conclusions: Frontal plane kinematics, specifically contralateral pelvic drop and femoral valgus, predicted the vast majority of the variance in 3D hip adduction during the stance phase of running. This indicates that 2D video may have potential as a clinically feasible proxy for measurement of peak 3D hip adduction – a risk factor for patellofemoral pain. Highlights: 3D peak hip adduction in running can be predicted from frontal plane kinematics. 2D peak pelvis and femur angles combined predict 3D peak hip adduction within 2.14°. Frontal plane kinematics do not predict 3D peak hip internal rotation in running.